Penyelenggaraan dan Tata Kelola Arsip Pada Record Center Fakultas Kedokteran Gigi Universitas Padjadjaran - Nur Indah Srirezeki; Sukaesih Sukaesih (BIBLIOTIKA : Jurnal Kajian Perpustakaan dan Informasi, 2023)
Organizing and managing records is very important in the management of information and documents. The Record Center of the Faculty of Dentistry, University of Padjadjaran is an institution that has duties and responsibilities in managing the document archives of the Faculty of Dentistry, University of Padjadjaran. The archive management system at the Record Center of the Faculty of Dentistry, University of Padjadjaran has been carried out properly and regularly, but there are still some obstacles to be faced, such as the lack of media equipment facilities. To overcome these obstacles, several efforts need to be made such as increasing storage on computers and improving facilities and infrastructure. With a good and organized record management system, it is expected to improve the performance and effectiveness of the Faculty of Dentistry, Padjadjaran University in managing documents and information related to academic and administrative activities.